Modulating the gut microbiota in Crohn’s disease: a pilot study on the impact of a plant-based diet with DNA-based monitoring - Østergaard, Stine Karstenskov; Cetin, Zeynep; Rasmussen, Henrik Højgaard; Lærke, Helle Nygaard; Holst, Mette; Lauridsen, Charlotte; Nielsen, Jeppe Lund (Frontiers in Nutrition, 2024)
Introduction Crohn’s Disease (CD) is characterized by chronic intestinal inflammation and dysbiosis. This study aimed to investigate the effects of a plant-based diet (PBD) on gut microbiota composition and inflammation in CD patients and assess the utility of trnL gene sequencing for monitoring dietary adherence. Methods Fourteen CD patients participated in a 12-week PBD intervention. Dietary adherence was monitored through self-reported food diaries and trnL sequencing, which detects plant residues in fecal samples. Gut microbiota was analyzed using 16S rRNA sequencing, and fecal calprotectin levels were measured as an indicator of intestinal inflammation. Results TrnL sequencing identified 55 plant genera in fecal samples, compared to 41 reported in food diaries, highlighting its accuracy in assessing plant residue diversity. By week 4, participants demonstrated a 1.4-fold increase in plant intake, correlating with a significant increase in microbial diversity. Key genera associated with gut health, such as Faecalibacterium and Bacteroides, increased in abundance. Additionally, fecal calprotectin levels decreased from 472 mg/kg at baseline to 207 mg/kg at week 12, indicating reduced intestinal inflammation. Discussion A PBD positively influenced gut microbiota composition and decreased intestinal inflammation in CD patients. The study also demonstrated that trnL sequencing is an effective tool for assessing dietary adherence in clinical settings, offering a more objective measure than self-reported food diaries.